Tafsir and Politics in Indonesia During the New Order Era: The Dialectic of Religious Texts and Power in an Authoritarian Regime - Maulana, Aldi Rifki; Safrudin, Ramadhan; Komarudin, Edi; Rohmana, Jajang A; Tarek Yalouli (JIA (Jurnal Ilmu Agama), 2026)
This study aims to examine the dialectical relationship between Qur’anic exegesis and political authority during the New Order era in Indonesia. Studies on Qur’anic exegesis in Indonesia have largely highlighted the influence of the socio-political context on the interpretive process. However, systematic studies that map the diverse responses of exegetical works to political power within a specific authoritarian regime remain relatively limited. Using a qualitative library research method with a descriptive-analytical approach, the study analyzes three representative Indonesian commentaries: Al-Qur’an dan Tafsirnya, published by the Ministry of Religious Affairs, Al-Huda by Bakri Syahid, and Dalam Cahaya Al-Qur’an by Syu‘bah Asa. The analysis employs Islah Gusmian’s typology of tafsir: silent tafsir, cosmetic tafsir, and critical tafsir combined with two analytical paradigms: the instrumentalization of tafsir and the actualization of divine values. The findings show that Qur’anic interpretation during the New Order reflects a spectrum of responses to political power, ranging from the depoliticization of Qur’anic verses that support political stability, the incorporation of state ideological language into religious discourse, to the articulation of ethical criticism toward authoritarian practices. These patterns demonstrate that tafsir functions as a contested discursive arena where religious meaning is negotiated within structures of power. Theoretically, this article extends Gusmian’s typology by proposing a relational and hybrid perspective of political tafsir, highlighting that Qur’anic interpretation may simultaneously accommodate and critique power depending on the socio-political position of the exegete. This study contributes to contemporary Qur’anic studies by offering a conceptual framework for understanding tafsir as a dynamic practice shaped by ongoing negotiations between revelation, authority, and socio-political context in modern Muslim societies.